The network structure of the CDS market and its determinants - Tuomas A. Peltonen; Martin Scheicher; Guillaume Vuillemey (European Central Bank (ECB), 2013)
This paper analyses the network structure of the credit default swap (CDS) market, using a unique sample of counterparties' bilateral notional exposures to CDS on 642 sovereign and financial reference entities. We study the network structure, similarly to the literature on interbank and payment systems, by computing a variety of network metrics at the aggregated level and for several subnetworks. At a reference entity level, we analyse the determinants of some key network properties for large reference entities. Our main results, obtained on a sub-sample of 191 reference entities, are the following. First, the CDS network shows topological similarities with the interbank network, as we document a “small world” structure and a scale-free degree distribution for the CDS market. Second, there is considerable heterogeneity in the network structures across reference entities. In particular, the outstanding debt volume and its structure (maturity, collateralization), the riskiness, the type (sovereign/financial) and the location (European/non-European) of reference entities significantly influence the size, the activity and the concentration of the CDS exposure network. For instance, the network on a high-volatility reference entity is typically more active, larger in size and less concentrated.
Keywords: G15; 330; Credit Default Swap (CDS); Financial networks; network determinants; network topology